2012
DOI: 10.1002/pfi.21264
|View full text |Cite
|
Sign up to set email alerts
|

The effect of users' attitudes on electronic performance support systems implementation

Abstract: Performance support (PS) platforms, also known as electronic performance support systems (EPSS), offer real‐time learning and performance enhancement. In 2008, Tel Aviv University and an Israeli telecommunication firm began researching implementation success factors. Preliminary findings and conclusions were discussed in an earlier Performance Improvement article (Gal & Nachmias, 2011). The current article focuses on the effects of users' attitudes on implementation issues and suggests a model for incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Rogers () indicates that individuals’ choices to adopt or reject an innovation are usually consistent with their attitudes toward it. Likewise, an earlier research study showed a strong positive relationship between users’ attitudes toward the EPSS and their willingness to use it in the future (Gal & Nachmias, ).
H5 : The police officers’ attitudes toward use significantly and positively influence their behavioral intentions to use the EPSS.
…”
Section: Hypotheses and Research Questionsmentioning
confidence: 77%
See 1 more Smart Citation
“…Rogers () indicates that individuals’ choices to adopt or reject an innovation are usually consistent with their attitudes toward it. Likewise, an earlier research study showed a strong positive relationship between users’ attitudes toward the EPSS and their willingness to use it in the future (Gal & Nachmias, ).
H5 : The police officers’ attitudes toward use significantly and positively influence their behavioral intentions to use the EPSS.
…”
Section: Hypotheses and Research Questionsmentioning
confidence: 77%
“…In general, attitudes toward a particular behavior play an important role in determining an individual's intention to perform it (Ajzen & Fishbein, ). Likewise, Gal and Nachmias () found that users’ attitudes toward the EPSS were strongly associated with their willingness to use it. Especially in mandatory use environments, attitude appears to have more importance in the acceptance of a system (Brown, Massey, Montoya‐Weiss, & Burkman, ; Yousafzai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tablet users also reported a high level of satisfaction from user experience aspects. According to Gal and Nachmias () these findings may indicate an increase of system adoption changes over time, provided that the success of the small‐scale pilot study will be repeated with larger groups of trainees, sharing the same characteristics and needs as the test groups.…”
Section: Discussionmentioning
confidence: 99%
“…An important parameter affecting the perception of the user is the user experience. A study by Gal and Nahmias () shows that labeling the support system as “help,” for example, lowered senior employees’ willingness to fully adopt a support system due to their assumption that they did not need help with core processes.…”
Section: A Theoretical Framework For Evaluating Performance Support Smentioning
confidence: 99%
“…Although the original definitions of performance support interventions focused on performance enhancement (Gery, ), some practitioners identified its potential to provide an effective real‐time learning platform (Barker, ; Gal & Nachmias, , ). The ability of users to retain information and skills following a PSS experience was supported empirically in the research conducted by Gal & Nachmias ().…”
Section: Performance Support As a Learning Strategymentioning
confidence: 99%